Antibiofilm Activity of Three Different Irrigation Techniques: An in Vitro Study - Caterina Eneide; Raffaella Castagnola; Cecilia Martini; Nicola Maria Grande; Francesca Bugli; Romeo Patini; Massimo Cordaro; Maurizio Sanguinetti; Giovanni Olivi; Gaetano Isola; Luca Marigo (MDPI AG, 2019)
The microbial infection of the endodontic space occurs in a necrotic tooth as a result of dental caries, trauma, periodontal disease, or previous root canal therapy. The disruption of the biofilms and the reduction of the bacterial load inside root canals are crucial for the success of root canal therapy. The aim of this study was to compare, in vitro, the antibiofilm efficacy of a novel passive sonic irrigation (PSI) device with passive ultrasonic irrigation (PUI) and conventional needle irrigation (CNI). Forty-four single-rooted human teeth were inoculated with a culture of E. faecalis for 28 days. The specimens were randomly divided into three groups: PUI, CNI, and PSI (n = 12). The activation protocols were performed using both 17% EDTA and 5.25% NaOCl. Residual bacterial biofilm was taken by means of a canal brush and colony-forming unit (CFU) were counted. The data were analyzed using one-way ANOVA and Games‐Howell’s post hoc tests. A major reduction in CFU was observed in the PSI and PUI groups, in comparison with the CNI group. No difference was found (p > 0.05) in terms of CFU reduction between PSI and PUI. PSI could be as effective as PUI in the removal of bacterial biofilms from straight root canals.